High intensity interval training vs. high-volume running training during pre-season conditioning in high-level youth football: a cross-over trial - Faude, O.; Schnittker, R.; Schulte-Zurhausen, R.; Müller, F.; Meyer, T. (Journal of Sports Sciences, 2013)
We aimed at comparing the endurance effects of high-intensity interval training (HIIT) with high-volume running training (HVT) during pre-season conditioning in 20 high-level youth football players (15.9 (s 0.8) years). Players either conducted HVT or HIIT during the summer preparation period. During winter preparation they performed the other training programme. Before and after each training period several fitness tests were conducted: multi-stage running test (to assess the individual anaerobic threshold (IAT) and maximal running velocity (Vmax)), vertical jumping height, and straight sprinting. A significant increase from pre- to post-test was observed in IAT velocity (P < 0.001) with a greater increase after HVT (+0.8 km/h vs. +0.5 km/h after HIIT, P = 0.04). Maximal velocity during the incremental exercise test also slightly increased with time (P = 0.09). Forty per cent (HIIT) and 15% (HVT) of all players did not improve IAT beyond baseline variability. The players who did not respond to HIIT were significantly slower during 30 m sprinting than responders (P = 0.02). No further significant differences between responders and non-responders were observed. Jump heights deteriorated significantly after both training periods (P < 0.003). Both training programmes seem to be promising means to improve endurance capacity in high-level youth football players during pre-season conditioning.